Determinant Of Consumer Repurchase Interest At Kober Mie Setan Jember - Abrori, Imam; Rijalus Sholihin, Muhammad (Jurnal Ilmu Manajemen Advantage, 2020)
This research is based on the influence of consumer repurchase interest in certain products. The case study in this research is the culinary product of Kober Mie Setan in the city of Jember. The research objective to be achieved is to test whether interest in repurchase interest is influenced by customization and consumer satisfaction with Kober Mie Setan products in Jember. This research uses quantitative methods. The number of samples used in this study were 77 people with a purposive sampling technique. The data was collected by means of a questionnaire. The analysis used includes instrument test data, multiple linear regression analysis. From the results of the data analysis, it can be seen that the adjustment of mass and customer satisfaction both simultaneously and partially has a positive and significant effect on repurchase interest.